Cocoa agroforestry systems in Africa – the art of reconciling sustainable production and ecological services - Jagoret, Patrick; Saj, Stéphane; Carimentrand, Aurélie (Perspective, 2020)
Version française de l'article Versión en español del artículo Combining mixed trees with cocoa trees in so-called cocoa agroforestry systems is emerging as a viable option for regenerating cocoa cropping in Africa. Pure cocoa crop stands currently prevail in these areas but are running out of steam. Technical solutions are therefore urgently needed to stabilize cocoa-growing areas, reduce pressure on forests and adapt to climate change. A balance can be struck in stands by combining cocoa trees with diverse trees chosen by farmers for their different uses, while maintaining a suitable and sustainable cocoa yield. Ecological services such as carbon storage and crop protection are co-benefits of this balance. Recent research in Cameroon highlights that cocoa agroforestry stands can be managed using a straightforward indicator—measurement of the basal area of cocoa trees and associated trees. This indicator could be adopted for sustainable cocoa production certification purposes, while the observed convergence between local know-how and scientific results could facilitate joint drawing up of technical recommendations.